Relational agility: Visualizing near-real-time Arctic sea ice data as a proxy for climate change. (October 2020) - Vardy, Mark
This ethnographic study at the US National Snow and Ice Data Center (NSIDC) follows a group of scientists and communications specialists as they compose visualizations and analyses of near-real-time Arctic sea ice data. Research participants collectively make scientific judgments about near-real-time data in a highly visible public venue with 'relational agility'. They balance multiple phenomena including knowledge of how sceptics attack climate science, reflexivity about the conventions through which sea ice data is gathered, the needs of journalists working in a news cycle paced by Twitter, and the liveliness and vitality of sea ice itself. Relational agility, understood as a way of coordinating the social in relation to this plurality of contingent practices and processes, provides insight into the science and politics of nonlinear climate change.